Study of fatigue behavior of cantilever piezoelectric energy harvester - Chen, Zhe (2014)
Piezoelectric energy harvesters generate electricity from ambient energy, which can in turn be used to power low-energy needed devices. It has been seen that some great improvements in using piezoelectric materials to collect energy have been achieved over the past several years, with a few products now commercially available. Energy harvester cantilever beams are capable to transform mechanical strain energy into electrical charge. However, a proper selection of the materials for the cantilever beams is very crucial. Since piezoelectric energy harvesters are extensively used in many electromechanical systems as sensing and actuating devices, the performance of these devices deteriorates due to cyclic loading. The decay in functional properties of materials over a period of repeated usage is called fatigue and this terminology is used to describe the loss in performance with time due to stress. The common phenomenon of fatigue is aging of the material, which affects the performance of the material with time. Output performance of piezoelectric harvesters would degrade accordingly with increasing levels of fatigue of the cantilever beams, whilst they are designated for a long term use. Hence there is a requirement to have an extensive study on its functional performance and properties. In this report, aluminum cantilever beam was tested. The beam consisted of piezoelectric materials in the form of MFC layers and the MFC layers harvest energy based on the d31 effect of the piezoelectric materials. The focus in this project is to have a better understanding of the induced fatigue of aluminum beam when it was subjected to a cyclic loading through the applications of impedance analysis and root-mean-square deviation statistic method. The change in open circuit voltage harvested has been measured by using relevant instrumentation from time to time. The gradual changes in fatigue level would result in a decrease in harvested energy. Meanwhile, analysis has also been done on impedance signatures for every acquisition. Comprehensive data obtained by real time experimentation is to be studied to reach a conclusion to state the suitability of the material of the cantilever beam for long term usage.